2020
DOI: 10.1101/2020.06.03.20121392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solar UV–B/A Radiation is Highly Effective in Inactivating SARS-CoV-2

Abstract: It is well known that 200-290 nm ultraviolet photons (hereinafter UV-C radiation) photo-chemically interacts with DNA and RNA and are endowed with germicidal properties that are also effective on viruses. Fortunately, Solar UV-C photons of this wavelength are filtered out by the Ozone layer of the upper Atmosphere, at around 35 km. Softer UV photons from the Sun with wavelengths in the range 290-320 nm (UV-B) and 320-400 nm (UV-A), however, do reach the Earth s surface. The effect of these photons on Single- a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…The efficiency of the solar-pump is here parameterized through the parameter ε (in the interval [0,1]) but depends, effectively, on internal virus properties, namely the lethal time τ 0 needed to deliver the UV lethal dose D 0 (defined as the UV-C fluence needed to inactivate 63% of the virus) for the given virus (Nicastro et al, 2020, submitted). At local noon (the minima of the daily solar curves of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency of the solar-pump is here parameterized through the parameter ε (in the interval [0,1]) but depends, effectively, on internal virus properties, namely the lethal time τ 0 needed to deliver the UV lethal dose D 0 (defined as the UV-C fluence needed to inactivate 63% of the virus) for the given virus (Nicastro et al, 2020, submitted). At local noon (the minima of the daily solar curves of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lytle and Sagripanti, 2005; Lubin and Jense, 1995) and the possible role they play on the seasonality of epidemics e.g Martinez, 2018), are nevertheless little studied. In two companion papers, we present a number of concurring circumstantial pieces of evidence suggesting that the evolution and strength of the recent Severe Acute Respiratory Syndrome (SARS-Cov-2) pandemics (Zhu et al, 2019; Cobey, 2020), might have been modulated by the intensity of UV-B and UV-A Solar radiation hitting different regions of Earth during the diffusion of the outbreak between January and July 2020 (Nicastro et al, 2020, submitted), and provide a measurement of the lethal UV-C dose for Covid-19 (Bianco et al, 2020, submitted).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pawar also indicates that although a strong relationship between recovered cases and death cases was observed, changes in temperature showed no signi cant correlation with con rmed cases in China by linear regression models (Pawar et al 2020). In addition, ultraviolet photons has also been considered to play the possible role in the modulation of COVID-19 epidemiology (Nicastro et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another study [3] pointed out that UV radiation will not be effective in places with high air pollution, where UV light turns into heat. On the other hand, other studies [4][5][6] have found that UV light is associated with decreased COVID-19 growth rate. Given the disagreement on the impact of UV light on COVID-19 transmission we take a fresh look at data for the UK.…”
Section: Introductionmentioning
confidence: 88%